On the use of sex steroids in women during the COVID-19 pandemic - T.F. Tatarchuk; Z.M. Dubossarska; V.I. Pyrohova; N.Y. Pedachenko; T.M. Tutchenko; O.О. Yefimenko; N.V. Kosei; Y.O. Dubossarska; K.L. Shatylovych; V.M. Zaporozhan; V.V. Kaminskyi; G.V. Zaichenko; et al. (Publishing House TRILIST, 2021)
The document was approved at an expanded meeting of the Ukrainian Society of Gynecological Endocrinology with the involvement of all board members and representatives of the Association of Obstetricians-Gynecologists of Ukraine, the Association of Pharmacologists of Ukraine, the Association of Anesthesiologists of Ukraine, as well during the Third Ukrainian School of Gynecological and Reproductive Endocrinology with international participation ISGE 19-20.03.21. The COVID-19 pandemic has significantly impacted medical practice, in terms of organizational and clinical practices, posing a number of complex and contradictory challenges for professionals. This document is the result of the systematization of scientific data available by March 2021 and recommendations of international medical and specialized professional societies on controversial clinical issues in gynecological practice caused by the COVID-19 pandemic, as well as certain issues of safety and ratio of using hormonal drugs. The involvement of experts from professional associations of the obstetric and gynecological field, pharmacology, anesthesiology and vascular surgery and phlebology in the working group made it possible to formulate clinically justified provisions of the position. The position includes three thematic sections: "On the use of estrogen-containing combined hormonal contraceptives (CHC) during the COVID-19 pandemic"; "On the use of menopausal hormone therapy (MHT) during the COVID-19 pandemic"; "On the issue of unregistered compounded bioidentical hormones". At the beginning of each thematic section, the main conclusions of the consensus position of professional medical associations are presented. According to the data available by March 2021, there is no reason to limit the use of CHC or MHT in healthy women (currently not having COVID-19). The question of CHC or MHT discontinuing or switching to other forms by women with COVID-19 should be decided depending on the severity of the disease, the total set of risk factors for thromboembolic complications and other individual characteristics of the clinical situation. Further research will provide elaboration of more detailed algorithms. Physicians need to be vigilant about the safety of compounded Bioidentical Hormonal Therapy (cBHT) in any dosage form (including pellets), especially during the COVID-19 pandemic, given the unexplored systemic effects and therefore the potential risks. Preference should be given to officially licensed medicinal products with a well-studied safety profile and clinical effects, the use of which is authorized by doctor's prescription and supported by clinical protocols and guidelines.